Ecoepidemiologia da febre maculosa em Minas Gerais, Brasil - Castro, Douglas Pereira (2012)
Introduction: Changes in epidemiological patterns and the consequent expansion of infectious diseases may be related to changes to environmental and seasonal variations in climate that influence the distribution of pathogens, vectors and reservoirs. Brazilian Spotted Fever (BSF) has as etiologic agent Rickettsia ricketsii, vectors are ticks of the Amblyomma and hosts are mammals such as capybara, echinus and tapirs. Humans acquire the disease by being bitten by infected ticks. Objectives: To analyze the spatial and temporal distribution of cases of BSF in the state of Minas Gerais (MG), using the reported and confirmed case by SINAN (Information System Notification of an appeal), from January 2001 to July 2010. Results: In the period 127 cases were reported in 38 municipalities of Minas Gerais, with the highest prevalence rate in Frei Gaspar (34:100.000) and municipalities with the highest number of cases were Belo Horizonte (26) and Juiz de Fora (17). The analysis by region revealed that the Belo Horizonte Metropolitan Region presented the highest number of cases of BSF, followed the region of Vale do Rio Doce and Zona da Mata. There was an increased number of cases in the months from May to November, highlighting the month of August. In 2008, there was an increased number of cases in relation to previous years. It is possible that the higher prevalence in certain months is related to the life cycle of the main vector of this disease A. cajennense, which has modified habitat preferences and their more infective stages (larva and nymph) increase in the driest periods of the year. Conclusion: The different types of climate and vegetation of the State of Minas Gerais may interfere with the distribution and expansion of the BFS, as it influences the life cycle of the vector. Further studies are needed to establish the role of prolonged droughts or excessive rainfall in disease transmission.